Kazakhstan : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper reviews economic developments in Kazakhstan during 1994-96. In early 1994, Kazakhstan embarked on an ambitious stabilization program aimed at reducing inflation sharply and implementing structural reforms. This program was based on tight financial policies and a package of structural measures, including privatization and trade and price liberalization; it was supported by a one-year stand-by arrangement from the IMF, approved in January 1994. However, the stabilization effort was quickly derailed by the authorities' inter-enterprise arrears netting operation that began in February 1994.